2019
DOI: 10.1016/j.actpsy.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

The sound of beauty: How complexity determines aesthetic preference

Abstract: Stimulus complexity is an important determinant of aesthetic preference. An influential idea is that increases in stimulus complexity lead to increased preference up to an optimal point after which preference decreases (inverted-U pattern). However, whereas some studies indeed observed this pattern, most studies instead showed an increased preference for more complexity. One complicating issue is that it remains unclear how to define complexity. To address this, we approached complexity and its relation to aes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…Unfortunately, here again, apart from anecdotal evidence, no experimental data are offered by the authors to corroborate their claim. Crucially, against FEP, numerous studies have shown that in esthetics (Delplanque et al 2019), music perception (Chmiel & Schubert 2017), visual perception (Chetverikov & Kristjánsson 2016), consumer behavior (Kao & Wang 2013), etc., humans have a preference for medium entropy patterns rather than low-entropy patterns. Entropy and liking follow an inverted U curve: expected (low entropy) patterns are judged to be boring, completely unexpected (high entropy) patterns are deemed too difficult/demanding, and medium entropy patterns are liked and looked for (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, here again, apart from anecdotal evidence, no experimental data are offered by the authors to corroborate their claim. Crucially, against FEP, numerous studies have shown that in esthetics (Delplanque et al 2019), music perception (Chmiel & Schubert 2017), visual perception (Chetverikov & Kristjánsson 2016), consumer behavior (Kao & Wang 2013), etc., humans have a preference for medium entropy patterns rather than low-entropy patterns. Entropy and liking follow an inverted U curve: expected (low entropy) patterns are judged to be boring, completely unexpected (high entropy) patterns are deemed too difficult/demanding, and medium entropy patterns are liked and looked for (cf.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, to further ensure we approached this endeavor from multiple angles, we used three different paradigms measuring preference for predictability. First, in the Music Preference paradigm (as developed by Delplanque et al, 2019), participants listened to specific tone sequences varying in predictability, followed by a forced-choice preference judgment task. Earlier findings show an inverted U-shape pattern, indicating strongest preferences for stimuli with medium complexity (Delplanque, De Loof, Janssens, & Verguts, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…First, in the Music Preference paradigm (as developed by Delplanque et al, 2019), participants listened to specific tone sequences varying in predictability, followed by a forced-choice preference judgment task. Earlier findings show an inverted U-shape pattern, indicating strongest preferences for stimuli with medium complexity (Delplanque, De Loof, Janssens, & Verguts, 2019). Second, we used a Perceptual Fluency paradigm in which predictability was manipulated subliminally.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of sound stimulus and sound preference was recognized as inverted-U pattern, which can achieve an optimal point. J. Delplanque et al studied the sound complexity and its relation to aesthetic preference and confirmed this century-old pattern [21]. Apart from multimedia contents, we are also exposed to the influence of aesthetic labor in various services.…”
Section: Product Aesthetic Modelingmentioning
confidence: 56%